Toward a cognitive science of markets: Economic agents as sense-makers - Samuel G. B. Johnson (Kiel Institute for the World Economy (IfW), 2019)
Behavioral economics characterizes decision-makers using psychologically-informed models. Cognitive science produces psychologically-informed models. Why don't these disciplines talk more? Here, the author presents several arguments for why cognitive science should inform behavioral economics - it characterizes internal psychological states, builds a richer conception of human nature, pays equal attention to cognition's successes and failures, embraces multidisciplinary insights, and avoids blind spots produced by behavioral economics' intellectual lineage. The author illustrates these principles using the cognitive science of sense-making - how humans understand information - including mental tools such as heuristics, stories, and theories. The science of mind can produce new insights to enrich economics.
Keywords: A12; B4; D01; D11; D7; D8; D9; E7; G4; 330; cognitive science; behavioral economics; experimental economics; behavioral finance; economics methodology; information processing; decision-making under uncertainty